Trails and technology: social and cultural geographies of abortion access - Calkin, Sydney; Freeman, Cordelia (Routledge, 2018)
Abortion is at once a routine medical procedure and the subject of intense controversy and unique criminal regulation. This provocation offers an account of the spatiality of abortion access and makes the argument that abortion implicates a range of social and cultural geography debates but has been generally overlooked in this field. It draws on two dominant forms of abortion mobilities to theorize a research agenda for geographies of abortion: the first section addresses abortion travel and its relational, embodied, and affective dimensions. The second section highlights the transformative impact of mobile medication abortion technology upon access and draws parallels between earlier debates on reproductive technology, medical control, and feminist cross-border resistance. The piece concludes by outlining productive research pathways for geographers with interests in gender, race, sexuality, and reproduction.